Recent Results on Science and Innovation Related to Electrical Processes of Thunderstorms - Christoph Köhn; Torsten Neubert; Martin Füllekrug; Ute Ebert; Sander Nijdam; Olivier Chanrion; Nikolai Østgaard; Martino Marisaldi; Serge Soula; Joan Montanyà; Francisco Gordillo-Vázquez; Alejandro Luque; et al. (Surveys in Geophysics, 2025)

Employing optical lightning data to identify lightning flashes associated to terrestrial gamma-ray flashes - Christoph Köhn; Matthias Heumesser; Olivier Chanrion; Victor Reglero; Nikolai Østgaard; H. J. Christian; T. J. Lang; R. J. Blakeslee; Torsten Neubert (Bulletin of Atmospheric Science and Technology, 2024)
Terrestrial gamma-ray flashes (TGFs) are bursts of energetic X- and gamma-rays emitted from thunderstorms. The Atmosphere-Space Interactions Monitor (ASIM) mounted onto the International Space Station (ISS) is dedicated to measure TGFs and optical signatures of lightning; ISS LIS (Lightning Imaging Sensor) detects lightning flashes allowing for simultaneous measurements with ASIM. Whilst ASIM measures $$\sim $$ ∼ 300-400 TGFs per year, ISS LIS detects $$\sim 10^6$$ ∼ 10 6 annual lightning flashes giving a disproportion of four orders of magnitude. Based on the temporal evolution of lightning flashes and the spatial pattern of the constituing events, we present an algorithm to reduce the number of space-detected flashes potentially associated with TGFs by $$\sim $$ ∼ 60% and of associated LIS groups by $$\sim $$ ∼ 95%. We use ASIM measurements to confirm that the resulting flashes are indeed those associated with TGFs detected at approx. 400 km altitude and thus benchmark our algorithm preserving 70–80% of TGFs from concurrent ASIM-LIS measurements. We compare how the radiance, footprint size and the global distribution of lightning flashes of the reduced set relates to the average of all measured lightning flashes and do not observe any significant difference. Finally, we present a parameter study of our algorithm and discuss which parameters can be tweaked to maximize the reduction efficiency whilst keeping flashes associated to TGFs. In the future, this algorithm will hence be capable of facilitating the search for TGFs in a reduced set of lightning flashes measured from space.

Climatology of Transient Luminous Events and Lightning Observed Above Europe and the Mediterranean Sea - Enrico Arnone; József Bór; Olivier Chanrion; Veronika Barta; Stefano Dietrich; Carl-Fredrik Enell; Thomas Farges; Martin Füllekrug; Antti Kero; Roberto Labanti; Antti Mäkelä; Keren Mezuman; et al. (Surveys in Geophysics, 2020)